KONDISI SOSIAL EKONOMI MASYARAKAT SUKU SAKAI DI DESA PETANI KECAMATAN BATHIN SOLAPAN KABUPATEN BENGKALIS - Rahmi, Putri Aulia; Isjoni, Isjoni; Ibrahim, Bedriati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Sakai tribe is a group of isolated people whi live traditionally in anarea on the island of Sumatera. Reside in the waters of the river, and they meet thenecessities of life by fishing. This study aims to determine the origin of the Sakai tribalcommunity in the Petani village, to find out the social conditions that are divided intohealth and education and to know the economic conditions of the Sakai tribe of thePetani village, the sub-district of Bathin Solapan, Bengkalis Regency. This study usesqualitative methods with data collection techniques in the form of observation,interviews and documentation.The result of this study indicate, (1)Sakai tribe came fromthe kingdom of Pagaruyung Minangkabau, west Sumatera in two waves of migration.The first arrival is expected to occur around the 14th century to the Mandau region,while the next arrivals are expected to arrive in Riau in the 18th century, who came tothe kingdome of Gasib. (2)The social conditions of the Sakai tribe in the Petani Villagesare still relatively low. This can be seen from the lack of health facilities and the lack ofpublic awareness of enviromental cleanliness. Besides that the condition of education isalso apprehensive, it can be seen from the many people who do not attend school andon average only graduate from elementary school. (3)The economic condition of thecommunity is low, this can be seen from the general income of the community is still lowand only comes from work as a fisherman. In general the Sakai tribe community in thePetani village already has a residence with its own ownership status, but the conditionof the building can be said to be unfeasible, besides that the Sakai tribe community alsodoes not have valuables such as vehicles and electronic equipment.Key Words: Social Conditions, Economic Conditions, The People of the Sakai Tribe